A influência da condição de entrada senoidal na dinâmica de golfadas na simulação de escoamento horizontal gás-líquido - Melo, Lucca Dalvi Vargas (2023)
There is a latent demand for developing numerical studies regarding two-phase slug flows in several industrial sectors, such as steel and food industries, and well designs in the oil and gas industry. Among the main challenges in the numerical modeling of this regime, one can highlight the development of a boundary condition that can adequately describe the main characteristics of the slugs. In this work, experimental data was generated and compared to numerical simulations of gas-liquid flows were performed using a sinusoidal inlet boundary condition with different perturbation amplitudes and slip ratios. The performed numerical simulations evidenced a significant effect of the slip ratio on the characterization of the slugs. For the case with a slip ratio greater than one, there was an increase in the frequency of slugs with decreasing perturbation amplitudes. Moreover, volume fraction levels show significant adherence to experimental results. For the no-slip case, experimental slug frequencies are simulated within a 2% range, regardless of perturbation amplitude and axial position. Interestingly, we observe a strong dependence of the characteristics of the bubble on the axial position of analysis. Deviations of the mean bubble periods with respect to experimental results may achieve 20%, depending on the axial position and the perturbation amplitude. The results suggest a preferred longitunal region for analysis since deviations smaller than 5% were found, regardless of perturbation amplitude. These results emphasize the importance of carefully analyzing slug characteristics regarding axial position.